A Foucault’s pendulum design - Salva, Horacio Ramon (2010)
In this article we explain our design and their performance, of a Foucault pendulum capable of continuous operation with a following system of the oscillation plane. We have built two pendulums, one of 2.835 m length and other of 4.975 m length. The oscillation amplitudes in either case were 1.8 and 1 deg, respectively. In our latitude the precession speed (9.89 deg/h counterclockwise) can be measured within 0.5 and 0.2 deg/h. The arrangement detected some earthquakes of medium intensity that took place as far as 765 km.